PEMAHAMAN AWAL ASPEK PERMINTAAN DARI KEGIATAN HUMAN TRAFFICKING - Kusumawardhani, D.T.P (P2KK LIPI, 2006)
This brief paper aims to explore trafficking demand using some perspectives from the field of marketing. It may seem invidious to use such terms when referring to human beings, but today there is a large and vibrant market for trafficked persons in a number of economic activities. Traffickers are regularly thinking of how to meet and stimulate the demand for their product. This has been an exploration of demand for trafficked people. It is based on very little hard evidence and only a working knowledge of marketing. The lack of information needed to address this question points to a profound need for better research all along the “product chain” of human trafficking, and especially with consumers of trafficking victims. Kata Kunci: Human Trafficking, Aspek Permintaan, Pemasaran Orang: Konteks Pasar Global dan Moral Ekonomi, Pararelisme dalam Atribut Korban, Penggunaan Kendali